Prevalence of IVIG resistance in Kawasaki disease: a systematic review and meta-analysis - Zou, Shuting; Hu, Bingyu (Frontiers in Pediatrics, 2025)
BackgroundKawasaki Disease (KD) is an acute vasculitis primarily affecting children, with intravenous immunoglobulin (IVIG) being the standard treatment and leading to increased risk of coronary artery abnormalities.ObjectiveThis systematic review and meta-analysis aim to evaluate the prevalence of IVIG resistance in KD and identify potential predictors and outcomes associated with this resistance.MethodsA comprehensive search of PubMed, Medline, Embase, and other relevant databases was conducted to identify studies reporting IVIG resistance in KD patients. Data on prevalence rates, patient demographics, and associated factors were extracted and analyzed.ResultsThe analysis included 26 studies with a total of 46,461 patients. The overall prevalence of IVIG resistance was found to be 14% (95% CI: 12%–16%), and The prevalence among males and females was 9% (95% CI; 7% to 10%) and 4% (95% CI; 3.7% to 4.3%), respectively.ConclusionIVIG resistance remains a significant challenge in the management of KD. Identifying patients at higher risk for IVIG resistance and developing alternative treatment strategies are crucial for improving outcomes in this population.